36.7k views
5 votes
Solve for x: -3x - 3 = - 12 ​

User JoshKopen
by
4.6k points

2 Answers

7 votes

Answer:

-3x-3=-12 +3

-3x=-9 ÷(-3)

x=3

Explanation:

prove me wrong

User Aaron Klotz
by
5.1k points
6 votes

Answer:

x = 3

Explanation:

-3x - 3 = -12

+3 +3

-----------------------

-3x = -9

-3x/3 = -9/3

-----------------------

-x = -3; x = 3

Check Work:

-3(3) - 3 = -12

-9 - 3 = -12

-12 = -12 (true)

User Polaris Nation
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.